2014
DOI: 10.1007/s11031-014-9465-7
|View full text |Cite
|
Sign up to set email alerts
|

Need for achievement moderates the effect of motive-relevant challenge on salivary cortisol changes

Abstract: The hypothalamic–pituitary–adrenal (HPA) axis plays a key role in the physiological response to stress, preparing the organism for appropriate action. While some research has examined universally relevant threats, other research has suggested that individual differences may moderate the relationship between stress and cortisol release, such that some individuals exhibit modified reactivity to personally relevant stressors or challenges. In the present study we investigated whether one individual difference—the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
0
10
0
3
Order By: Relevance
“…nPower was associated with a greater cortisol response in the psychosocial-stress group, a lower cortisol response in the control condition, and no observed change in the physical-stress condition. In a challenging social-evaluative cognitive task with positive, negative, or neutral bogus feedback, nAchievement did not predict cortisol response overall; however, nAchievement dampened the cortisol response in the negative-feedback condition ( Yang, Ramsay, Schultheiss & Pang, 2015 ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…nPower was associated with a greater cortisol response in the psychosocial-stress group, a lower cortisol response in the control condition, and no observed change in the physical-stress condition. In a challenging social-evaluative cognitive task with positive, negative, or neutral bogus feedback, nAchievement did not predict cortisol response overall; however, nAchievement dampened the cortisol response in the negative-feedback condition ( Yang, Ramsay, Schultheiss & Pang, 2015 ).…”
Section: Resultsmentioning
confidence: 90%
“…The link between nAffiliation and cortisol was also equivocal, with positive , negative (Wegner et al, 2014), andnonsignificant (McClelland et al, 1987) associations reported. nAchievement provided a more consistent relationship, predicting a dampened cortisol response during a visuomotor competition, during the TSST, and in response to negative feedback (Schultheiss et al, 2014, Studies 1 and 2;Yang et al, 2015). However, there were also experimental studies in which this relationship was not observed (Wiemers et al, 2015;.…”
Section: Discussionmentioning
confidence: 99%
“…Naše výsledky dále do jisté míry podporují zjištění studií, které dokazují, že adolescenti vystavení v minulosti opakovanému negativnímu stresu vykazují nižší hladiny kortizolu než ti, kteří tak často stresovým situacím vystaveni nejsou (Hostinar & Gunnar, 2013;Jaffee et al, 2015). Vezmeme-li v úvahu, že sledované zátěžové situace jsou ve škole víceméně pro všechny žáky stejné, pak tedy rozdíly v tom, jakým způsobem se s nimi adolescenti vyrovnávají, jsou zřejmě ovlivněny řadou dalších faktorů, na které upozorňovaly i studie sledující souvislost mezi výkonem během zátěžové situace a produkcí kortizolu (Schultheiss et al, 2014;Yang et al, 2015). Tento jev však nebyl doposud uspokojivě vysvětlen.…”
Section: Diskuseunclassified
“…However, implicit motives are not only related to the individual's behavior, but also to psychophysiological responses such as the release of hormones (implicit power motive: testosterone and estradiol; implicit achievement motive: cortisol and vasopressin; implicit affiliation motive: dopamine and progesterone; McClelland et al, 1987 ; Schultheiss and Rohde, 2002 ; Schultheiss, 2013 ; Schultheiss et al, 2014 ; Yang et al, 2015 ). In addition, implicit motives are associated with specific health outcomes such as stress, changes in blood pressure and immune parameters (McClelland, 1989 ; Baumann et al, 2005 ; Schüler et al, 2009 ; Job et al, 2010 ; Brandstätter et al, 2016 ).…”
Section: Implicit Motives and Their Originsmentioning
confidence: 99%